Description Of Low Back Pain Functional Activities In Students Politeknik Unggulan Kalimantan - Aulia Nanda Viyanti; Yulisha Eva Oktaviani; Enny Fauziah; Arfian Hamzah (UPPM Politeknik Unggulan Kalimantan, 2024)
Students are a group of people who spend more time in static positions. This can be seen during lecture hours and doing assignments. Students spend more time in a sitting position with less attention to posture, resulting in musculoskeletal disorders such as low back pain. Low back pain is pain caused by disorders or abnormalities in the elements of the muscles, nerves, structures or joints. The symptoms in this condition are pain, muscle weakness, and limited movement. Complications of these symptoms result in impaired functional activity in the vertebrae. The purpose of this study is to find out the description of the functional activity of low back pain in the superior polytechnic students of Kalimantan. The benefit of this research is to add knowledge and insight about how Low Back Pain Functional Activities are Described in Kalimantan Excellence Polytechnic Students. The method used in this study is a type of quantitative research with a descriptive research design. This research was conducted to describe the functional activities of students who experience low back pain by using the Oswestry Disability Index (ODI). The results of this study showed that it mostly occurred at the age of 21 years (33.69%), female sex (63%), Physiotherapy study program (29.34%), the most common type of low back pain was myogenic low back pain (98%) ), functional activity with mild interpretation (98%) and normal body mass index (72%).